Development of a DC-DC buck boost converter using fuzzy logic control - Shaban Jaber, Fathi (2011)
A fuzzy controller of DC-DC Buck-boost converter is designed and presented in this project. In order to control the output voltage of the buck-boost converter, the controller is designed to change the duty cycle of the converter. The mathematical model of buckboost converter and fuzzy logic controller are derived to design simulation model. The